Pengaruh Latihan Depth Jump dan Knee Tuck Jump terhadap Peningkatan Kekuatan Otot Tungkai pada Siswa Putra Ekstrakurikuler Voli di SMA 2 Ngadirojo Pacitan - Nugroho, Ahmad Rizal Bayu, Dwi Rosella K, S,Fis., M.Fis, Arif Pristianto, SSt.FT.,M.Fis (2016)
Muscle strength is the maximum ability of muscles to contract. In volleyball, leg muscle strength is one that plays an important role during the movement jumps (jumping). Because one of the engineering components and characteristics of volleyball is a jump, then jump the supporting muscle strengthening exercises should be considered to optimize the performance of athletes during the game in order to get a good jumping ability. Stimulate cell activation motor muscle fibers needed a proper exercise technique, one of them exercise plyometric.In this study, researchers applied depth training methods knee tuck jump and jump. The purpose of this study was to determine the effects of exercise depth knee tuck jump and jump to the increase in leg muscle strength in male students in high school extracurricular volleyball 2 Ngadirojo Pacitan. This research method using quasi-experimental approach, with a design in the form of pre-test-post-test two group design. The population in this study were all male students at SMAN 2 Ngadirojo totaling 22 respondents, then divided into two groups, with a treatment depth jump as much as 11 respondents, and the group treated with knee tuck jump as much as 11 respondents. Test the effect of using the Wilcoxon test to determine the effect of pre and post test while using a different test of Mann Whitney. The results showed a depth jump plyometric exercises influence on the leg muscle strength with the value 0.003, there is the influence of plyometric exercises knee tuck jump to the leg muscle strength with the value 0.003, no difference between the depth jump plyometric exercises and knee tuck jump to the leg muscle strength with the value 0,450.